Not just money. How organised crime, violence, and insecurity are shaping emigration in Mexico, El Salvador, and Guatemala - Cutrona, Sebastián A. (International journal of comparative and applied criminal justice, 2023)
This article utilises logistic regression analysis to determine the factors that influence people from Mexico, El Salvador, and Guatemala deciding to flee to other countries. By broadening the traditional migration literature, we argue that organised crime, violence, and insecurity, not purely economic calculations, play a crucial role in one’s decision to emigrate to the U.S. Although concretely economic motivations, such as the household’s wage level, and social capital-related factors like having family ties in the destination country, are strong correlates in our models, we show that victimisation and fear of crime also affect the decision to live or work abroad. We contend that these factors are directly related to the presence of gangs and other criminal organisations in all three countries.